Upaya Membangun Kedisiplinan Belajar Peserta Didik - Siburian, Hendro Hariyanto; Seliyah, Seliyah (Sekolah Tinggi Teologi Sumatera Utara, 2023)
Discipline in learning is one of the factors in achieving learning goals. Disciplinary problems also occur in class 1 SDK Transformasi students. This indiscipline results in the learning outcomes determined by the school needing to be achieved as contained in the school's curriculum vision and mission. This research method uses descriptive qualitative methods. The aim of this research is to describe the important role of teachers and parents in developing student discipline. The results of this research are that teachers must carry out their roles and functions well, and teachers must also collaborate with students' parents in developing students' discipline. Educators and parents build cooperation through agreement and communication, involvement in decision-making, and parenting. Elements of education and parents work together in an effort to build learning discipline in grade 1 SDK Transformasi students. AbstrakKedisiplinan dalam belajar merupakan salah faktor tercapainya tujuan belajar. Permasalahan disiplin juga terjadi pada peserta didik kelas 1 SDK Transformasi. Ketidakdisiplinan tersebut mengakibatkan capaian pembelajaran yang ditentukan sekolah tidak tercapai sebagaimana yang termuat pada kurikulum serta visi dan misi sekolah. Metode penelitian ini menggunakan metode kualitatif deskriptif. Tujuan dari penelitian ini adalah mendeskripsikan peran penting guru dan orangtua dalam mengembangkan kedisiplinan peserta didik. Hasil dari penelitian ini adalah guru harus melakukan peran dan fungsinya dengan baik, guru juga harus bekerjasama dengan orangtua peserta didik dalam mengembangkan kedisiplinan peserta didik. Pendidik dan orangtua membangun kerjasama yang di dalamnya ada kesepakatan dan komunikasi, keterlibatan dalam pengambilan keputusan, dan parenting. Unsur pendidikan dan orangtua bersinergi dalam upaya membangun kedisiplinan belajar peserta didik kelas 1 SDK Transformasi.